Measuring the age-friendliness of cities in the Russian Federation: The translation, validation and application of the age-friendly cities and communities Questionnaire in the city of Kazan - Liliya E. Ziganshina; Aizyara F. Garaeva; Liliya I. Talipova; Rustem N. Khairullin; Jeroen Dikken; Joost van Hoof (Heliyon)
Numerous cities in the Russian Federation have joined the World Health Organization's (WHO) Global Network for Age-Friendly Cities and Communities since 2011. In order to do quantitative evaluations of the age-friendliness of cities, the Age-Friendly Cities and Communities Questionnaire (AFCCQ) was developed in the Netherlands. The purpose of this study was to translate and test the validity and reliability of the AFCCQ for use in the Russian Federation, and to study the views on the age-friendliness of the city of Kazan in the Republic of Tatarstan from an intergenerational perspective. Data were collected in a survey. In total, 208 people from various age cohorts met the inclusion criteria to assess the psychometric validity. Confirmatory factor analysis supported the structure with nine factors. Overall, the people in Kazan experience the age-friendliness of their city as positive. The youngest and oldest generations demonstrated the most positive scores. Only for the domain of respect and social inclusion results were reversed. The Russian language version of the AFCCQ proved a valid and reliable instrument to evaluate age-friendliness of cities and communities in Russia. Data gathered through the instrument can be used as input for planning, implementing and further monitoring of age-friendly initiatives in the country.